Development of Narrate c by using Knowledge Story Construction Process Framework - Nurzairin binti Mustaffa, Nurzairin (Universiti Teknologi Petronas, 2012)

(untitled)
This project proposes the usage of Knowledge Story Constrtrction Process Framework and Knowledge Story Constnrction Process Model in knowledge capturing and sharing practices within IT & Media Services (ITMS) departrnent in Universiti Teknologi PETRONAS. Since knowledge is an asset to an organizatioru preserving knowledge is the most important element to be focused on nowadays. This knowledge is tacit knowledge which lies on people's mind usually based on their experiences. Tacit knowledge is often transferred through stories and these knowledge stories are usually not stnrctured and preserved. These stories are commonly based on procedural, declarative and episodic knowledge. The proposed franrework and model aims to help repackage tacit knowledge into a more struchrcd way so that the knowledge can be hansferred effectively. The author has conductd data gathering and analysis on the knowledge sharing prrctices as well as thc usage of Knowledge Story Constmction Process Model within ITMS departrnent. It is identified that storytelling is the most preferred way for knowledge sharing and the model is efficient for knowledge capture. The development of NarrateC (stards Narrative Constructor) which is a narrative constnrction application systern is an initiative to preserve the knowledge as well as the platform for knowledge sharing. Knowledge Story Construction Process Model is implemented in fte NarrateC to help the users in structuring their knowledge stories.